High-Performance Solid-Phase Extraction Chromatography for Recycling of NdFeB Magnet Waste - Tiaan Punt; Kerstin Forsberg; Michael Svärd (Materials Proceedings)
The increasing use of rare-earth elements (REEs) in renewable technologies such as electric vehicles and wind turbines is driving a rapid rise in their economic importance. This work investigated the separation of REEs (Nd, Pr, Sm, and Dy) from NdFeB magnets using high-performance solid-phase extraction chromatography. More than 99% of the REEs were extracted from an Fe-rich sulfate-based leach liquor using a three counter-current stage solvent extraction of 34.7 vol.% and O/A 1.5. The REE-loaded H2SO4 strip solution was separated into a high-purity Nd and Pr fraction from separate Sm and Dy fractions in a single stage using a D2EHPA-impregnated column and H2SO4 gradient elution.